From the part-of-speech definition in grammar to the part-of-speech label in lexicography - Snoj, Jerica (Slovenski jezik / Slovene Linguistic Studies, 2019)
In dictionaries, part-of-speech labelling represents a substantial segment of lexicographic descriptions. Although it is based in the grammar of a particular language, it must follow the concept of each particular dictionary. In recent decades, noticeable progress in the theoretical discourse on word classes in Slovenian may be observed. While fulfilling other lexicographical demands (the structure of the lexical unit, lexical meaning, categorial semantic features), modern Slovenian dictionary-making could also consider new conceptions of Slovenian word classes developed by recent studies. In respect to part-of-speech labelling, dictionaries of Slovenian are not uniform; this fact might be taken into consideration by authors of new Slovenian lexicographic manuals.